Identification of common epitopes on gliadin, enterocytes, and calreticulin recognised by antigliadin antibodies of patients with coeliac disease - Krupicková, S; Tucková, L; Flegelová, Z; Michalak, M; Walters, J R; Whelan, A; Harries, J; Vencovský, J; Tlaskalová-Hogenová, H (Gut, 1999)
BACKGROUND: Sera of patients with coeliac disease, containing IgA and IgG antigliadin antibodies (AGA) and various IgA autoantibodies, react with isolated enterocytes. AGA cross react with enterocyte antigens, one of which has been identified as calreticulin. AIMS: To characterise the antigenic structures of gliadin, enterocytes, and calreticulin recognised by AGA from patients with active coeliac disease. METHODS: AGA were isolated from sera of nine patients by affinity chromatography and tested by competitive ELISA using 40 alpha-gliadin synthetic dodecapeptides (A1-F6). RESULTS: Reactivity of gliadin with all purified AGA tested was inhibited by peptide A4 at the N-terminal region; by C2, C3, and D4 at the central region; and by F3 and F4 at the C-terminal region of the gliadin molecule. AGA cross reactivity with enterocytes was inhibited by peptides A4, D1-D4, and F6 and with calreticulin by peptides A4, D3, and D4. As dominant epitopes AGA of coeliac patients recognise similar structures corresponding to peptides A4, D3, D4, and F6 present on gliadin, enterocytes, and calreticulin. Substitution of glutamine in the A4 peptide by glutamic acid caused loss of inhibitory capacity. Shortening of peptide A4 on the N-terminal by three amino acids increased its inhibitory effect. CONCLUSIONS: AGA of patients with coeliac disease react with similar structures on gliadin and potential autoantigens on enterocytes.
Keywords: Cross Reactions; Celiac Disease; střeva; autoimunitní nemoci; protilátky; Rats, Wistar; zkřížené reakce; ribonukleoproteiny; Gliadin; Epitopes; gliadin; Adult; kalretikulin; dospělí; epitopy; potkani Wistar; celiakie; Autoantigens; autoantigeny; ELISA; Calreticulin; peptidové fragmenty; krysa rodu Rattus; chromatografie afinitní; Antibodies; Animals; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; Humans; zvířata; Calcium-Binding Proteins; Rats; Ribonucleoproteins; proteiny vázající vápník; Autoimmune Diseases; Intestines; Peptide Fragments; Female; Chromatography, Affinity